Strategic Management of General Secondary Schools Modeling Processes (Eurasian Journal of Learning and Academic Teaching, 2023)
Today, the design of management and co-management processes in a comprehensive school is considered a natural necessity. The practice of managing educational institutions shows the importance of modeling not only educational processes, but also management processes and cooperative management. The implementation of the strategic approach technology in the process of managing a general education school requires a certain sequence to achieve the intended results. This, in turn, determines the need to develop management models, defined as an effective means of achieving strategic goals and rational organization of management activities. Management models are developed to implement two: functional tasks and strategic goals in a certain sequence. Accordingly, the typological characteristics of strategic goals determine the two-level classification of management models.belgilaydi